Pengembangan bahan ajar materi pendidikan bagus ngaji dan dagang (Gusjigang) melalui Media Filmora 9 di MI NU Ittihadul Falah Kedungdowo Kudus - Moh. Sukri; Saadi Saadi (At Turots: Jurnal Pendidikan Islam, 2022)
This study aims to evaluate the needs analysis in the production of teaching materials, the steps for making teaching materials, the quality of products and facilities, and the level of product effectiveness. Gusjigang is a mindset that adheres to racial and cultural differences in class IV Madrasah Ibtidaiyah NU Ittihadul Falah Kedungdowo, Kaliwungu, Kudus Regency. The method used in Research and Development (R&D) research. To make certain products, research is used which includes needs analysis and checking the feasibility of a product. This research is divided into three stages to assess the effectiveness of local learning, which include: 1) To determine the current character learning model, the preliminary (research) stage is descriptive qualitative; 2) Preparation of model design, validation of model 1 (experts/experts), and validation of model 2 (practitioners) through FGD (Focus Group Discussion) to produce a hypothetical model is part of the design development stage (development); 3) Limited scale trial phase (disseMadrasah Ibtidaiyahnasi), which ends in the production of the final model as a finished product and publication. The results of the research are 1) The validation assessment of material experts on the attitude of accepting ethnic and cultural diversity is included in the valid category and is very suitable for use; 2) The media expert validator commented on three aspects, namely a) Media in making filmora 9 videos in supporting learning is used for learning using story scenarios in material that accepts ethnic and cultural diversity, material adapted to Core Competencies and Basic Competencies; b) Should show audio-visual media in learning, so that the display is more attractive and motivates students to learn more; 3) The assessment in the feasibility test on a limited scale of learning media is in the category of proper use; 4) Development of teaching materials using the story method based on local wisdom gusjigang through filmora 9 media can improve student learning outcomes in the subject of accepting ethnic and cultural diversity effectively